CXCR5‐CXCL13 axis markers in full‐term and preterm human neonates in the first weeks of life. Issue 5 (9th February 2021) - Pietrasanta, Carlo; De Leo, Pasqualina; Jofra, Tatiana; Ronchi, Andrea; Pugni, Lorenza; Mosca, Fabio; Aiuti, Alessandro; Cicalese, Maria Pia; Fousteri, Georgia
Abstract : Term and preterm neonates have very few circulating Tfh‐like cells (cTfh), and no circulating Tfr‐like cells. Neonatal cTfh are CXCR5 lo PD‐1 lo CD45RA hi, suggestive of a naive, possibly recently activated phenotype. CXCL13 is high at birth, but decreases rapidly in the first weeks of life. Overall, signs of GC activity in human neonates are weak, even in those born prematurely or after sepsis.